Reflections on the justiciability of the "national security" clause as stipulated by section 18A of the Competition Act 89 of 1998: Lessons from Russia - Measures Concerning Traffic in Transit WTO Panel Decision - Tavuyanago, Simbarashe; Vinti, Clive (Law, democracy & development, 2023)
This article discusses the justiciability of the national security clause of the Competition Act 89 of 1998, which was introduced through recent amendments to the merger regulation framework The clause provides for the executive, through the establishment of a national security committee, to intervene in mergers which may pose a threat to national security interests of the country. The national security committee will have authority to determine whether a proposed merger may be approved, approved subject to conditions, or prohibited. International practice does permit national security concerns as one of the public interest considerations in the assessments of a merger involving a foreign firm. However, section 18A of the Competition Act fails to provide a clear guideline for recourse for parties to a merger that has been deemed to be in contravention of the provision. Consequently, this article assesses the justiciability of the national security clause in section 18A of the Competition Act by advancing the approach of the WTO Panel in Russia - Measures Concerning Traffic in Transit. In the light of this, it is our view that the decision of the national security committee to prohibit a merger based on national security interests could be challenged by an aggrieved party, even though the Act makes no provision for such a scenario on the grounds of the correlative principles of rule of law, legality and legal certainty, as well as the inherent jurisdiction of our higher (in relative terms) courts.